A Naked-Eye Fluoride Ion Recognition Based Vanilin Derivative Chemosensors - R Rahmawati; Bambang Purwono; Sabirin Matsjeh (Chemistry Education Program, the University of Mataram, 2019)
Two new receptors S2 and S6 were designed and synthesized based on benzimidazole and azo-benzimidazole synthesized from vanillin for the colorimetric detection of fluoride ion. The presence of nitro group in S2 and azo in S6 makes –OH proton (binding site) acidic and therefore it could deprotonate with addition of basic anion such as fluoride. Hydroxyl (–OH) functionality which detects basic fluoride ions via hydrogen-bonding mechanism wich is mechanism involved in the color change of receptor R2 and R6, its mean that initial hydrogen bond formation of F− ion with –OH group.